Perkawinan Semu dalam Perspektif Pidana Keimigrasian - Arya Mulia; I Wayan Prasetya Lencana; Janitra Seskoaria (Universitas Batanghari Jambi, 2021)
Indonesia has become one of the destination countries for foreigners because of many factors that make foreigners come, many foreigners want to obtain Indonesian citizenship. There are many ways that foreigners can do in obtaining Indonesian citizenship, one of which is by conducting pseudo-marriages. In the enforcement of immigration law against pseudo-marriage, immigration has an important role related to proving the crime by using Law No. 6 of 2011 as a reference, the crime of pseudo-marriage until now is difficult to prove the criminal elements, but before that happens Immigration can prevent by being more careful in issuing immigration documents.